The complex longitudinal influence of paternal and maternal parental psychological flexibility on child problem behavior: exploring the role of parenting styles - Baocheng Pan; Youli Wang; Pin Xu; Yizhao Gong; Chengli Zhao; Jiaxuan Miao; Yan Li (BMC Psychology)
Abstract Purpose This study aims to explore the complex relationship between paternal and maternal parental psychological flexibility, parenting styles, and child problem behavior within the cultural context of China. Methods Structural equation modeling was used to conduct statistical analysis on longitudinal data from 893 parent-child pairs in Shanghai. Results The study found a significant negative correlation between maternal parental psychological flexibility and child problem behavior, with maternal authoritative and authoritarian parenting styles mediating this relationship. Conversely, paternal parental psychological flexibility exhibited no significant direct impact on child problem behavior, possibly influenced by traditional gender roles and the primary caregiver effect. Conclusions This research extends the Reactance-Inhibition Model and the Spillover Hypothesis Theory, elucidating the complex dynamics of family interactions. Practical implications underscore the importance of interventions such as Acceptance and Commitment Therapy (ACT) and professional parenting training to enhance parental flexibility and implement effective parenting styles. Overall, this study contributes to understanding family dynamics and informs strategies for promoting healthy child development within different cultural contexts.